Development of a Digital Literacy Based E-Module in Informatics Subject to Improve Student Learning Outcomes - Nasution, Haris; Napitupulu, Efendi; Sinaga, Enny Keristiana (UNDIKMA, 2025)
This study aims to design and develop a digital literacy-based e-module for the Informatics subject to improve student learning outcomes at MTsN 3 Langkat. The developed module aims to: (1) Determine the feasibility of the e-module; (2) Determine the practicality of the e-module; (3) Determine the effectiveness of the e-module; (4) Identify the differences in student learning outcomes between those who use the digital literacy-based e-learning module and those who use conventional modules; (5) Identify differences in learning outcomes based on visual, auditory, and kinesthetic learning styles; and (6) Examine the interaction between the digital literacy-based e-learning module and learning styles in influencing student learning outcomes. The population of this study includes all eighth-grade students at MTsN 3 Langkat. The sampling technique used is cluster random sampling. The research design employed is a 2x3 factorial design, and the data analysis technique used is two-way analysis of variance (ANOVA). This study obtained the results of the e-module which was feasible, practical, effective, there were differences in learning outcomes in the module groups, learning styles and there was interaction.